Simpustronik: A Management Strategy for Health Service Efficiency and Reducing Bureaucracy in Health Centers - Putri, Cici Yuliza (BKM Public Health and Community Medicine, 2024)
Purpose: The implementation of the Electronic Community Health Center Information System (Simpustronik) aims to reduce bureaucracy and enhance the efficiency of healthcare services in community health centers (Puskesmas) in Indonesia. Content: Simpustronik replaces the manual recording and reporting system with an integrated digital system, encompassing patient registration, electronic medical records, service scheduling, and drug inventory monitoring. The impact of implementing Simpustronik includes increased operational efficiency, reduced patient waiting times, and more responsive and integrated healthcare services. The main challenges in its implementation are the lack of bureaucratic innovation, limited infrastructure and facilities, and effective hierarchical coordination. However, with government regulatory support and improvements in information technology infrastructure, Simpustronik can overcome these obstacles. Conclusion: Simpustronik has shown significant potential in improving the efficiency and quality of healthcare services at Puskesmas. Effective management strategies, such as socialization, training, and collaboration with various stakeholders, are crucial to ensuring the successful implementation of this program.